2018
DOI: 10.5897/ajb2017.16267
|View full text |Cite
|
Sign up to set email alerts
|

Optimized production of phytase by solid-state fermentation using triticale as substrate and source of inducer

Abstract: This study was carried out to evaluate the process of phytase production by Aspergillus niger in solidstate fermentation (SSF) using triticale waste. A waste that currently has no use was reported for this biotechnological process, and is of high impact due to the null use. The process was carried out using an additive free medium, supplemented with only one nitrogen source. Under these conditions, phytase activity of 7.45 U/g dry substrate (DS) was obtained. The process was optimized using different additives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, Sabu et al (2002) have reported on phytase production by R. oligosporus on coconut oil cake substrate in SSF. In a recent study, triticale waste was used as a substrate for the evaluation of phytase production by A. niger (Neira-Vielma et al, 2018). Additionally, phytase production was investigated by SSF using mixed substrates.…”
Section: Sources and Production Of Fungal Phytasesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Sabu et al (2002) have reported on phytase production by R. oligosporus on coconut oil cake substrate in SSF. In a recent study, triticale waste was used as a substrate for the evaluation of phytase production by A. niger (Neira-Vielma et al, 2018). Additionally, phytase production was investigated by SSF using mixed substrates.…”
Section: Sources and Production Of Fungal Phytasesmentioning
confidence: 99%
“…Phytase production using different fungal strains is affected by differing culture conditions (Qasim et al, 2017;Neira-Vielma et al, 2018). Optimum conditions for the production of phytases obtained from different fungal strains have been established by changing both nutrient and physical conditions.…”
Section: Sources and Production Of Fungal Phytasesmentioning
confidence: 99%
See 1 more Smart Citation